Research on Treating Insomnia Accompanied With Depression by Mongolian Medical Warm Acupuncture - Bao, Lidao; Li, Sha; Jin, Qiu; Si, Lengge; Bo, Agula (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2018)
Objective To observe the therapeutic effect of Mongolian medical warm acupuncture in treating the patients with insomnia accompanied with depression and discuss the mechanism of action of Mongolian medical warm acupuncture in treating insomnia.Method 50 patients with insomnia accompanied with depression were clinically selected and randomly divided into the Mongolian medical warm acupuncture group and the drug group (trazodone) of 25 each. The patients in the Mongolian medical warm acupuncture group were subjected to acupoint stimulation (Xin acupoint, Dinghui acupoint, and Heyi) for 30 min once a day. 100mg of trazodone were administered to the patients in the drug group. The patients in both groups were treated for 4 weeks. The patients in both groups were compared in terms of Pittsburgh sleep quality index, sleep quality, daytime functions, self-rating depression scale etc.Result There was a significant difference in total score of Pittsburgh sleep quality index (PSQI) between the patients in the Mongolian medical warm acupuncture group before treatment (16.83±3.68) and those after treatment (8.18±3.78)(P<0.01). The scores of sleep quality and daytime functions of the patients in the Mongolian medical warm acupuncture group (6.76±2.76) were superior to those in the drug group (5.89±2.87)(P<0.05). The self-rating depression scale (SDS) scores of the patients in the Mongolian medical warm acupuncture group after treatment (0.54±0.89) decreased significantly when compared with those before treatment (P<0.01). There was no significant difference in clinical therapeutic effect between both groups (P=0.0812>0.05). The obvious curative rate in the Mongolian medical warm acupuncture group (75.58%) was significantly superior to that in the drug group (49.77%) (P=0.0382<0.05). The Asberg side effect rating scale (SERS) score in the drug group after treatment (6.11±2.06) was significantly higher than that in the Mongolian medical warm acupuncture group (4.15±1.98) (P<0.05).Conclusion Mongolian medical warm acupuncture has therapeutical effect on insomnia accompanied with depression and Mongolian medical warm acupuncture has better therapeutical effect and fewer side effects than trazodone. Mongolian medical warm acupuncture has certain sedative-hypnotic and anti-depressive effects applies to insomnia accompanied with suppression.Ziel Feststellung der therapeutischen Wirkung von heißer Akupunktur nach Mongolischer Medizin in der Behandlung von Patienten mit Insomnie in Verbindung mit einer Depression und Diskussion der Wirkungsmechanismen dieser Akupunkturtechnik bei der Behandlung von Insomnie.Methode 50 Patienten mit Insomnie in Verbindung mit einer Depression wurden klinisch ausgewählt und zufällig in 2 Gruppen zu je 25 Personen eingeteilt, wobei eine Gruppe mit heißer Akupunktur nach Mongolischer Medizin und die andere Gruppe medikamentös (Trazodone) behandelt wurde. Die Patienten in der Akupunktur-Gruppe wurden einmal pro Tag für eine Dauer von 30 Min. mit Akupunkturpunkt-Stimulation (Xin Akupunkturpunkt, Dinghui Akupunkturpunkt und Heyi) behandelt. Die Patienten der anderen Gruppe erhielten 100 mg Trazodone. Beide Gruppen wurden über einen Zeitraum von 4 Wochen behandelt. Die Patienten beider Gruppen wurden mithilfe des Pittsburgh Schlafqualitätsindex bezüglich Schlafqualität, Leistungsfähigkeit am Tag, Selbstbeurteilung der Depression usw. verglichen.Ergebnis Die Gesamtauswertung des Pittsburgh Schlafqualitätsindex (PSQI) bei der Akupunktur-Gruppe ergab eine signifikante Differenz zwischen dem Zustand der Patienten vor der Behandlung (16,83 ± 3,68) und nach der Behandlung (8,18 ± 3,78) (P < 0,01). Schlafqualität und Leistungsfähigkeit am Tag waren bei den Patienten, die mit heißer Akupunktur nach Mongolischer Medizin (6,76 ± 2,76) behandelt wurden, besser als bei den Patienten, die medikamentös behandelt wurden (5,89 ± 2,87) (P < 0.05). Bei der Selbstbeurteilungsskala von Depressionen (SDS self-rating depression scale) gaben die Patienten der Akupunktur-Gruppe nach der Behandlung einen signifikanten Rückgang der Depression an (0,54 ± 0,89) im Vergleich zu ihrem Zustand vor der Behandlung (P < 0,01). Bezüglich der klinisch therapeutischen Wirkung gab es keinen signifikanten Unterschied zwischen beiden Gruppen (P = 0,0812 > 0,05). Die offensichtliche Heilungsrate in der Akupunktur-Gruppe (75,58 %) war signifikant höher als diejenige in der medikamentös behandelten Gruppe (49,77 %) (P = 0,0382 < 0,05). Der Fragebogen zur Erfassung von Nebenwirkungen nach Asberg (SERS – side effects rating scale) ergab in der medikamentös behandelten Gruppe nach der Behandlung (6,11 ± 2,06) einen signifikant höheren Score als in der Akupunktur-Gruppe (4,15 ± 1,98) (P < 0,05).Schlussfolgerung Heiße Akupunktur nach Mongolischer Medizin zeigte eine therapeutische Wirkung auf Insomnie in Verbindung mit einer Depression und zeigte im Vergleich zur Behandlung mit Trazodone eine bessere therapeutische Wirkung und weniger Nebenwirkungen. Heiße Akupunktur nach Mongolischer Medizin hat eine sedierend-hypnotische und anti-depressive Wirkung in der Behandlung von Insomnie in Verbindung mit einer Depression.
Keywords: Mongolian medical; warm acupuncture; insomnia; depression